On the organic law of change : a facsimile edition and annotated transcription of Alfred Russel Wallace's Species notebook of 1855-1859 - Wallace, Alfred Russel, 1823-1913 (Harvard University Press, 2013)
Notes from Wallace's Malay expedition.